Web-Based Ornamental Chicken Delivery Service Information System: Sistem Informasi Jasa Kirim Ayam Hias Berbasis Web - Kurnianto, Happy; Hindarto, Hindarto (Universitas Muhammadiyah Sidoarjo, 2022)
Technology in the era of modernization is developing very quickly, making humans face various changes, in terms of information systems that are increasingly rapidly following the times. With the rapid advancement of technology. Companies are competing to take advantage of technology to be the best. One of the service jobs that is quite widely used is the provider of ornamental chicken delivery services, where these services can help people who want to send their chickens between cities and outside the island. This information system was created with the aim of making it easier for managers to conduct transactions and collect customer data. This information system is built using PHP technology and MySQL database. Making this information system uses the waterfall method where researchers analyze the current system to find deficiencies or problems from the current system and then look for solutions to overcome these problems. Based on the results of the tests that have been carried out, the system built can run well and meet the needs of CV. Dwi Atmojo in providing convenience in processing customer data and recording transactions that occur. With this information system, users can record customer data, record transactions and confirm payments as well as monitor delivery status.